Optimalisasi Optimalisasi Kemampuan Komunikasi Matematis Melalui Pendekatan TaRL Ditinjau Dari Minat Belajar Peserta Didik - Utami, Ulfany Fitri; Laelasari; Maharani, Anggita; Hartono, Wahyu (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This research aims to determine the optimization of students' learning interest by using TaRL (Teaching At The Right Level) learning which is viewed from the learning interest of students in class X. The research method used in this research is quantitative descriptive. Data on students' learning interest was measured using a questionnaire and data on the results of mathematical communication skills through written tests, both of which were analyzed quantitatively. The results showed that the average percentage of interest in learning increased by 23% from 49% (less) in cycle I to 72% (sufficient) in cycle II. In the aspect of students' mathematical communication skills, it is demonstrated by an increase in the percentage of completeness by 33% in cycle I to 82% in cycle II. The average student score increased by 48% from Cycle I to Cycle II.